2023
DOI: 10.3389/fmicb.2023.1115449
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate determines the bacterial habitat specialization and impacts microbial functions in a subsurface karst cave

Abstract: Karst caves are usually considered as natural laboratories to study pristine microbiomes in subsurface biosphere. However, effects of the increasingly detected nitrate in underground karst ecosystem due to the acid rain impact on microbiota and their functions in subsurface karst caves have remained largely unknown. In this study, samples of weathered rocks and sediments were collected from the Chang Cave, Hubei province and subjected to high-throughput sequencing of 16S rRNA genes. The results showed that nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 140 publications
0
8
0
Order By: Relevance
“…4 ). These genera include Actinomadura (Lipski & Altendorf 1995 ; Lin et al 2022 ), Actinophytocola , (Zhang et al 2014 ; Liu et al 2023a ), Azoarcus (B. Liu et al 2006 ; Lee et al 2014 ; Li et al 2020 ), Luteitalea (Pessi et al 2022 ), Mesorhizobium (Siddiqi et al 2019 ), and Streptomyces (Feng et al 2014 ; He et al 2021 , 2022 ). Under the assumption that these bacterial communities were active in R CTRL and ammonia (NH 4 − ) was present (likely due to animal excreta and/or decaying organic matter), nitrification may have been coupled to Mn reduction (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ). These genera include Actinomadura (Lipski & Altendorf 1995 ; Lin et al 2022 ), Actinophytocola , (Zhang et al 2014 ; Liu et al 2023a ), Azoarcus (B. Liu et al 2006 ; Lee et al 2014 ; Li et al 2020 ), Luteitalea (Pessi et al 2022 ), Mesorhizobium (Siddiqi et al 2019 ), and Streptomyces (Feng et al 2014 ; He et al 2021 , 2022 ). Under the assumption that these bacterial communities were active in R CTRL and ammonia (NH 4 − ) was present (likely due to animal excreta and/or decaying organic matter), nitrification may have been coupled to Mn reduction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The anoxic bio-oxidation pathway of NH 4 − in the presence of MnOx was first observed by Hulth et al ( 1999 ). Microbial-mediated manganese redox cycling for the simultaneous removal of NO 3 − /NO 2 − and NH 4 − , along with micropollutants, has recently gained growing interest (Liu et al 2023a , b ; Zhong et al 2023 ). However, since we did not quantify nitrogen species during reactor operation, this remains a hypothesis, the testing of which will require further research.…”
Section: Discussionmentioning
confidence: 99%
“…The reason could be NO 3 À -N is a nutrient and electron acceptor in oligotrophic soil conditions (Kimble et al, 2018). The enhancement of N availability may decrease the abundance of nitrogen-fixing microbes and increase nitrophilous taxa (Liu et al, 2023). The accumulation of NO 3 À -N can lead to soil acidification (Chen et al, 2019).…”
Section: Forest Succession's Effects On the Bacterial α Diversitymentioning
confidence: 99%
“…In addition, oxygen concentration, light condition, temperature, metal and organic compound also contribute to their distinct ecological niche differentiation in natural environments ( Liu et al, 2015 ; Ouyang et al, 2017 ; Cheng et al, 2019 ; Khanom et al, 2021 ). The isolation and relative stable conditions create specific microhabitats within caves, especially loose sediments on the ground and weathered rocks of the cave passage ( Cheng et al, 2023 ; Liu X. Y. et al, 2023 ), providing excellent conditions for the exploration of the niche differences of ammonia-oxidizing microorganisms in oligotrophic environments. However, the distribution of AOA and AOB and the ecological processes responsible for their development in these unique microhabitats remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological guilds exhibit different community structures due to different responses to environmental selection ( Zhao et al, 2019b ). Studies have clearly demonstrated the strong niche specificity of bacterial communities in loose sediments and those living on weathered rocks ( Cao et al, 2021 ; Liu X. Y. et al, 2023 ) as well as for methanotrophs ( Cheng et al, 2022 ), which may be also true in microbial functional groups involved in nitrification. If it is the case, what ecological processes contribute to the differences in ammonia-oxidizing communities in different niches in karst caves?…”
Section: Introductionmentioning
confidence: 99%